Prognostic importance of apathy in syndromes associated with frontotemporal lobar degeneration. (2nd April 2019) - Lansdall, Claire J.; Coyle-Gilchrist, Ian T.S.; Vázquez Rodríguez, Patricia; Wilcox, Alicia; Wehmann, Eileen; Robbins, Trevor W.; Rowe, James B.
Abstract : Objective: To determine the influence of apathy, impulsivity, and behavioral change on survival in patients with frontotemporal dementia, progressive supranuclear palsy, and corticobasal syndrome. Methods: We assessed 124 patients from the epidemiologic PiPPIN (Pick's Disease and Progressive Supranuclear Palsy, Prevalence and Incidence) study. Patients underwent detailed baseline cognitive and behavioral assessment focusing on apathy, impulsivity, and behavioral change. Logistic regression identified predictors of death within 2.5 years from assessment, including age, sex, diagnosis, cognition, and 8 neurobehavioral profiles derived from a principal component analysis of neuropsychological and behavioral measures. Results: An apathetic neurobehavioral profile predicted death (Wald statistic = 8.119, p = 0.004, Exp(B) = 2.912, confidence interval = >1 [1.396–6.075]) and was elevated in all patient groups. This profile represented apathy, weighted strongly to carer reports from the Apathy Evaluation Scale, Neuropsychiatric Inventory, and Cambridge Behavioral Inventory. Age at assessment, sex, and global cognitive impairment were not significant predictors. Differences in mortality risk across diagnostic groups were accounted for by their neuropsychiatric and behavioral features. Conclusions: The relationship between apathy and survival highlights the need to develop more effective and targeted measurement tools to improve its recognition and facilitate treatment. The prognostic importance of apathy suggests that neurobehavioral features might be useful to predict survival and stratify patients for interventional trials. Effective symptomatic interventions targeting the neurobiology of apathy might ultimately also improve prognosis.